(untitled) (Research, Society and Development, 2021)
Objective: to carry out an integrative review of the role of pharmacists in vaccination services so that they accept, claim, and adopt a greater role in promoting vaccination in Brazil. Methods: This is an integrative literature review on the practice of vaccination services by pharmacists. Results: It was found that pharmaceutical services are in increasing evolution, however, there are few studies that indicate vaccination services by pharmacists in the country. Providing high vaccine coverage and the inclusion of new health institutions, such as pharmacies and/or drugstores, has made possible the globalization of vaccinations, including the introduction of new vaccines in the poorest countries in the world. The pharmacist and his team play a fundamental role in providing quality pharmaceutical assistance and/or care. They are responsible for ensuring the implementation of access to medication, such as vaccines, as both the professional and their assistants enable actions that allow users to better understand their health, their medications, their therapeutic project, and their needs. Conclusion: The pharmacist has significant importance, together with other professionals, in immunization services. In Brazil, these professionals exercise the legal right and technical competence to perform this service and the immunization performed by pharmacists in pharmacies and/or drugstores, in addition to consolidating clinical practice, contributed to access and increase vaccination coverage rates in the country.